Integrated RF front-end circuits and antennas for next generation wireless communication systems - Tan, Eng Leong. (2008)
Integrated RF front-end circuits and antennas can lead to configurations that are reduced in loss, size and cost, yet featuring high performance and advanced functionalities. Such integration finds potential applications in recent communication technologies such as MIMO, UWB and ROF. This research project investigates into the combined field-circuit analysis techniques for integrated circuit-antenna modules. Novel unconditionally stable and efficient techniques are devised, namely alternatingdirection-implicit finite-difference time-domain (ADI-FDTD) method including lumped circuit elements, and unconditionally stable analysis approach for circuit networks.